Differential protein abundance in promastigotes of nitric oxide‐sensitive and resistant Leishmania chagasi strains. Issue 11 (14th October 2016) - Alcolea, Pedro J.; Tuñón, Gabriel I. L.; Alonso, Ana; García‐Tabares, Francisco; Ciordia, Sergio; Mena, María C.; Campos, Roseane N. S.; Almeida, Roque P.; Larraga, Vicente
Abstract : Purpose: Leishmania chagasi is the causative agent of zoonotic visceral leishmaniasis in Brazil. Domestic and stray dogs are the main reservoirs. The life cycle of the parasite involves two stages. Promastigotes are extracellular and develop within the sand fly gut. Amastigotes survive inside the harsh environment of the phagolysosome of mammalian host phagocytes, which display the nitric oxide defense mechanism. Surprisingly, we were able to isolate promastigotes that are also resistant to NO. This finding may be explained by the preadaptative hypothesis. An insight into the proteome of NO‐sensitive and resistant promastigotes is presented herein. Experimental design: Total protein extracts were prepared from promastigote cultures of an NO‐sensitive and a resistant strain at early‐logarithmic, mid‐logarithmic and stationary phase. A population enriched in metacyclic promastigotes was also isolated by Percoll gradient centrifugation. In vitro infectivity of both strains was compared. Differential protein abundance was analyzed by 2DE‐MALDI‐TOF/TOF. The most striking results were tested at the mRNA level by qRT‐PCR. Three biological replicates were performed in all cases. Results: NO‐resistant L. chagasi promastigotes are more infective than NO‐sensitive ones. Among the differentially abundant spots, 40 proteins could be successfully identified in the sensitive strain and 38 in resistant promastigotes. Conclusions and clinical relevance: The increase of G6PD and the decrease of ARG and GPX transcripts and proteins contribute to NO resistance in L. chagasi promastigotes. These proteins may be studied as potential drug targets and/or vaccine candidates in the future.